Makna Pragmatis pada Judul Artikel Surat Kabar MALUT POST dan POSKO MALUT - Abdullah, Suhardi (Universitas Sam Ratulangi, 2013)
Study which used in this research is Malut Post and Posko Malut as mass media of jurnalistic aims to (1) To identify and classify the type of pragmatic meanings titles in a newspaper of Malut Post and Posko Malut. (2) To identify and analyze the pragmatic meaning in the newspaper article. (3) To explain why the pragmatic meanings used in the title of both newspaper. This research use descriptive qualitative method. Procedure data collected by using observation, technical note and interview techniques to identify the types of pragmatic meanings used the theory of pragmatics (implicature, presupposition, and speech acts). Based on the analysis conclussion are implicature, speech acts, presuppositions, illocutionary and perlocution speech acts. Article titles contain the news about politics and government, crime, moral issues, economic and development activities, health and prosperity of society, welfare, education, technology, sports, human interest, and war and diplomacy. Conclusions on this research that some factors caused by pragmatic meanings should be use with briefly, concise, effective, and interesting. Other while the message of information delivered with through, concise, clear, easy to understand and interesting. With the hope of pragmatic meanings uses in language learning needs in schools from primary to university level. Key words: pragmatics meaning, title, newspaper articles